2014
DOI: 10.1159/000371611
|View full text |Cite
|
Sign up to set email alerts
|

Speech Performance and Training Effects in the Cochlear Implant Elderly

Abstract: Objectives: Cochlear implantation requires acclimatization to the electrical input. Usually, cochlear implant (CI) listeners undergo an auditory rehabilitation program that includes auditory training sessions. Recently, it was shown that a phoneme-based training may improve speech perception abilities even in experienced CI listeners. The current study focuses on whether the effect of an auditory training program depends on the age of CI listeners. Design: Fifteen CI listeners took part in an auditory phoneme-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
0
14
1
2
Order By: Relevance
“…By omitting the need of specific equipment beyond training CDs, however, the approach proposed and evaluated here is very cost‐effective. As noted before, a final potential source of bias is the fact that mostly motivated patients take part in studies like the present one. Therefore, the effect shown here might partially depend on the supposed high motivation of the patients.…”
Section: Discussionmentioning
confidence: 89%
“…By omitting the need of specific equipment beyond training CDs, however, the approach proposed and evaluated here is very cost‐effective. As noted before, a final potential source of bias is the fact that mostly motivated patients take part in studies like the present one. Therefore, the effect shown here might partially depend on the supposed high motivation of the patients.…”
Section: Discussionmentioning
confidence: 89%
“…Further, elderly CI listeners also demonstrate benefit from individually tailored auditory training therapy that can result in auditory outcomes marginally below those observed for younger CI users [Schumann et al, 2014].…”
Section: Discussionmentioning
confidence: 97%
“…Previously, in both CI users and the NH group, the attentional modulation of auditory cortical responses has been revealed during SiN perception [ 31 , 32 ]. In people with hearing impairment and CIs, aural rehabilitation focusing on attention-induced change has been effective in improving speech understanding with background noise [ 14 , 33 ]. A number of studies comparing the cortical responses recorded from passive and active listening reported that N1 and P2 amplitudes increased with attention [ 9 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%